Devenir chrétienne à Carthage (IIe – IIIe siècle) - Laetitia Ciccolini (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
The investigation centres on a comparaison of Tertullian’s attitudes toward women with those of Cyprian of Carthage. While women are often addressed as recipients or referred to in Tertullian’s works, they seem to be forgotten by the bishop of Carthage. The way the two north African writers speak of the path of conversion can explain why we sense less of a concern with women in Cyprian’s works. Tertullien makes a connection between conversion and their natural status ; it is a reason why women are singled out et why he offers to them specific instruction and spiritual guidance, even if he does not apply a double standard in matters of ethical behaviour. Cyprian focused on the integrity of the faith of the new Christians, on the importance of preserving the prescriptions of the Lord. He is concerned with their commitment in their new life, which seems to be the only relevant category.